Critical characteristics of technique in throwing the discus - Hay, J. G.; Yu, B. (Journal of Sports Sciences, 1995)
The purpose of this study was to identify those characteristics of the techniques used by elite discus throwers that are most closely related to the distances they record. The subjects were the competitors in the discus throw events at two major meetings. Two S-VHS video cameras were used to record the performances of the subjects; the direct linear transformation (DLT) procedure was used to obtain three-dimensional data from these records. For the males, the change in speed of the discus during the second double support phase was more influential than the change in speed during any other phase in accounting for differences in the distances of the throws recorded. For the females, the changes in speed during the flight phase and during the second double support phase were about equally influential in accounting for differences in the distance thrown. The findings suggest that emphasis placed on achieving a large change in the speed of the discus during the second double support phase is well founded; that the speed of release is the most influential determinant of the distance of the throw; and that, in most cases, the aerodynamic forces exerted on the discus during the flight increase the distance of the throw.